Dynamic Change of Heme Environment in Soluble Guanylate Cyclase and Complexation of NO‐Independent Drug Agents with H‐NOX Domain. (26th December 2012) - Alisaraie, Laleh; Fu, Yangxin; Tuszynski, Jack A.
<x xml:space="preserve">Abstract</x> Soluble guanylate cyclase is a heterodimer receptor that functions in several signal transduction pathways. Conversion of guanosine 5′‐triphosphate to 3′, 5′‐cyclic monophosphate second messenger at the catalytic domain is regulated by the changes at heme nitric oxide/oxygen domain of the β‐subunit. To better understand conformational changes at heme site that may impact on activities of catalytic domain, three soluble guanylate cyclase homolog proteins with heme at Fe‐His state were investigated, and their dynamic behaviors were monitored in both unliganded (apo) and complex with heme. As a result of dynamic conformational changes, Lys110, Asp45, Arg135, and Glu41 were found interacting with the site gate, which may interfere with transportation of small molecules in and out of the heme site. An alternative binding site adjacent to that of heme was identified. Binding affinity of several nitric oxide‐independent activators and heme‐dependent stimulators was examined, and their binding modes in the heme site and in the alternative binding site in the human soluble guanylate cyclase enzyme were computationally simulated. The calculated binding energies were used as criteria to filter results of virtual high‐throughput screenings based on FlexX ligand–docking algorithm and absorption, distribution, metabolism, excretion, and toxicity properties on databases of available drugs. The identified drugs from virtual high‐throughput screening have been suggested for experimental investigations, based on which they may either be directly repurposed or require structural modifications for better physico‐chemical and pharmacological properties.